The treasure of Jamaica reef - Stone, Virginia L.; Boyd, Stephen, 1931-1977; Walker, John, 1956 April 21-; Cinetel Films ([New York, NY] : D & R Film Project : Producers Group Inc., 1975)
Off the coast of Jamaica, lies a sunken Spanish galleon with a fortune in gold waiting to be recovered. Unfortunately, there is a curse upon the treasure and bad things have happened to anyone who's tried to find it. Scuba diver Hugo Graham sets out to find and recover the treasure but soon discovers a deadly guardian over the wreck site, a large grey shark.
Based on: Diary of a diver / by John Walker.
Stephen Boyd, David Ladd, Chuck Woolery, Rosey Grier, Darby Hinton, Cheryl Stoppelmoor, Art Metrano.
Editor, Virgina Stone; music, Christopher Lively Stone.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Treasure troves -- Jamaica -- Drama; Action and adventure films; Feature films; Internet videos; Streaming video